2004
DOI: 10.1073/pnas.0308432101
|View full text |Cite
|
Sign up to set email alerts
|

A concise, total synthesis of the TMC-95A/B proteasome inhibitors

Abstract: A concise, total synthesis of the proteasome inhibitors TMC-95A͞B has been accomplished. The synthesis features the use of an L-serine-derived E-selective modified Julia olefination reaction to ultimately control the stereochemical outcome of the highly oxidized tryptophan fragment. Additionally, the limited use of protecting groups at a late stage of the total synthesis allowed for its completion in an efficient manner.Julia olefination ͉ Suzuki biaryl coupling ͉ Stille coupling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Garners aldehyde [39] and the corresponding bromide), but most of these reactions yielded an epimeric mixture of the compounds. We then used Kocienski-modified Julia olefination (Scheme 1), [40] utilizing an aldehyde 9 [41] and a sulfone 10, [42] both of which were derived from d-serine. The reaction proceeded without epimerization to give the key intermediate 11, which was converted to the protected meso-DAP 12 and 13.…”
Section: Resultsmentioning
confidence: 99%
“…Garners aldehyde [39] and the corresponding bromide), but most of these reactions yielded an epimeric mixture of the compounds. We then used Kocienski-modified Julia olefination (Scheme 1), [40] utilizing an aldehyde 9 [41] and a sulfone 10, [42] both of which were derived from d-serine. The reaction proceeded without epimerization to give the key intermediate 11, which was converted to the protected meso-DAP 12 and 13.…”
Section: Resultsmentioning
confidence: 99%
“…In this approach, we chose to employ 5-phenyl-tetrazolyl (PT) sulfone 9 (prepared following a modified procedure reported by Albrecht et al 31 ), as it has been reported to be less prone to self-condensation than the benzothiazolyl sulfone. 32 The synthesis of 3b is described in Scheme 1.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Synthetic organic chemists have shown considerable interest in TMC-95A because of its unusual chemical structure, its potency and its unique inhibition mechanism [189]. Several total syntheses have been achieved, but they have not provided sufficient material for broad biological evaluation [190][191][192]. Simpler and more accessible TMC-95 macrocyclic analogues 39-42 have been synthesized in order to explore their SAR (figure 20) [185,186,[193][194][195][196][197][198][199].…”
Section: Tmc-95 and Derivativesmentioning
confidence: 99%